Exploitation of different technical scientific knowledge in optical systems for safety increasing in transportation - KOVÁČIK, Peter (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
The article draws attention to using of headlights at different modes and with various sources of light. There are mentioned systems controlled by electronics for mostly active safety of an automobile caused by optimal illumination of road. From mentioned above results aim of the article - suggest to necessity of early and high quality preparation of specialists at field of automo-bile electronics.